Hydrologic implications of GRACE satellite data in the Colorado River Basin1. Issue 12 (24th December 2015) - Scanlon, Bridget R.; Zhang, Zizhan; Reedy, Robert C.; Pool, Donald R.; Save, Himanshu; Long, Di; Chen, Jianli; Wolock, David M.; Conway, Brian D.; Winester, Daniel
Abstract: Use of GRACE (Gravity Recovery and Climate Experiment) satellites for assessing global water resources is rapidly expanding. Here we advance application of GRACE satellites by reconstructing long‐term total water storage (TWS) changes from ground‐based monitoring and modeling data. We applied the approach to the Colorado River Basin which has experienced multiyear intense droughts at decadal intervals. Estimated TWS declined by 94 km 3 during 1986–1990 and by 102 km 3 during 1998–2004, similar to the TWS depletion recorded by GRACE (47 km 3 ) during 2010–2013. Our analysis indicates that TWS depletion is dominated by reductions in surface reservoir and soil moisture storage in the upper Colorado basin with additional reductions in groundwater storage in the lower basin. Groundwater storage changes are controlled mostly by natural responses to wet and dry cycles and irrigation pumping outside of Colorado River delivery zones based on ground‐based water level and gravity data. Water storage changes are controlled primarily by variable water inputs in response to wet and dry cycles rather than increasing water use. Surface reservoir storage buffers supply variability with current reservoir storage representing ∼2.5 years of available water use. This study can be used as a template showing how to extend short‐term GRACE TWS records and using all available data on storage components of TWS to interpret GRACE data, especially within the context of droughts. Key Point: GRACE Total Water Storage was extended to 1980 showing 50–100 km 3 depletions related to droughts